Assessment of quality of life in parents of epileptic children and its associated factors - Goti, Ashish; Dihora, Rameshkumar; Desai, Sweta (International Journal of Contemporary Pediatrics, 2020)
Background: Aim of the study was to assess quality of life (QOL) of parents of epileptic child and its association with various factors like demographic, clinical, therapeutic and behavioral factors. Methods: Consenting parents of 160 epileptic children were enrolled after finishing child’s visit to the pediatrician. Parents were enquired on baseline demographic variables like age, gender, socio-economic status, parental education; clinical details like type of epilepsy, duration of seizure, seizure frequency and co-morbidity and therapeutic factors like treatment of epilepsy and adverse drug reactions. QOL was evaluated using QOLCE questionnaire and Childhood Illness-related Parenting Stress Inventory and analysed. Results: Out of 160 parents, 85% belong to 30-40 years of age and 62.5% were male. Deteriorated quality of life was reported by parents as mean score 63.46±7.69. QOL was significantly poor (p<0.05) in parents of younger child (<6 yrs), education status (upto primary school only), employment status of parent (unemployed) and lower socioeconomic status. Assessment of disease related parameters revealed that type of seizure, seizure frequency, duration and co-morbidity were factors significantly affecting quality of life of parents with lower QOL scores(p<0.05). QOL of parents of child with epilepsy undergoing polytherapy with multiple AEDs treatment, particle seizure control and having adverse drug reaction were associated with poor scores of health and well being (p<0.05). It was found that parents of epileptic child had deteriorated QOL score with respect to behaviour patterns irrespective to conditions of epilepsy due to constant stress and anxiety and poor state of mind. Conclusions: QOL of parents was compromised in Indian children with epilepsy. Demographic factors like age of child, parental education, socio-economic status and clinical factors like type of seizure, frequency & duration of seizure and co-morbid conditions significantly affect the QOL of parents. Significantly poor QOL scores was also due to therapeutic factors like treatment with polytherapy and adverse drug reactions with poor behavioral patterns which was observed in parents that should be taken care and should not be overlooked.